Compiler Construction for a Network Identification - Soni, Sumit; Kumar, Pravesh (Journal of Advance Research in Electrical & Electronics Engineering (ISSN 2208-2395), 2014)
The Compiler Construction is mainly used to improve the network processing system through the advance advance compiler design.The name Compiler is primarily used for programs that translate source code from a high –level programming language to a lower level language.The advance compiler design is useful in the industrial application like telecommunication. Our approach to increase the flexibility ,productivity and usability of the system to target with the minimal effort .we use the bit level addressing for the network processor we show how a compiler backend has been design and also improve the feature of the compiler and fully operational. A compiler is a computer program (or set of programs) that transforms source code written in a programming language (the source language) into another computer language (the target language, often having a binary form known as object code The most common reason for wanting to transform source code is to create an executabe program.